Hubungan Pengetahuan, Minat dan Sikap Mengajar dengan Kesediaan Mengajar Matematik Awal Berasaskan Pendekatan STEM dalam Kalangan Guru Prasekolah - Mohd Ikhlas Bin Abd. Halim; Nordin Bin Mamat; Nor Mashitah Mohd Radzi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Teachers are the main agent to ensure the integration of STEM approach in Early Mathematics education at the preschool level is successfully implemented.  This study determines the extent to which the preschool teachers are ready to teach Early Mathematics based on STEM approach. This study also aims to determine the relationships of knowledge, interest and teaching attitude with teaching readiness among preschool teachers. The research used a descriptive and quantitative design that involved 253 preschool teachers selected using stratified random sampling from five districts in Sabah, namely, Sandakan, Telupid, Ranau, Tuaran and Penampang. Data obtained from questionnaires were analyzed with IBM SPSS version 26.0 using Pearson Correlation. Findings of the study showed that the preschool teachers perceived teaching knowledge and readiness highly but teaching interest and attitude were perceived moderately. The relationships of knowledge, interest and teaching attitude with teaching readiness were positive and significant but the strength of correlation differs whereby knowledge correlated highly with teaching readiness but interest and attitude correlated poorly with teaching readiness for Early Mathematics based on STEM approach. These findings encourage more efforts to improve teaching interest and attitude through intervention such as provision of extrinsic compensation, implementation of continuous teacher professionalism development program that focuses on digital media and sophisticated technology usage as well as creation of conducive school culture. These strategic efforts are hoped to enhance knowledge, interest and attitudes of the preschool teachers and carry out their responsibilities in realizing STEM education to teaching Early Mathematics.